Faktor-Faktor yang Berhubungan Dengan Pengetahuan Ibu tentang Pijat Bayi di RSUD Kota Sabang - Nur Fatimah; Nila Diana; Nova Sasmita; Nur Jannah; Nurlaila Nurlaila; Tiarnida Nababan (Universitas Malahayati Lampung, 2025)
ABSTRACT Infant massage has many health benefits, one of which is the quality of infant sleep. Baby massage is not only done when the baby is healthy, but also when the baby is sick or fussy and has become a routine for baby care after birth The purpose of this study was to determine the factors associated with maternal knowledge about baby massage. The type of research used is quantitative using an analytic observational design research design with a cross sectional approach. The population in this study were all mothers who had babies 0-12 months who visited the Sabang City Hospital totaling 105 people. The subject retrieval technique used purposive sampling of 84 people. The data collection method used was by using a questionnaire that was prepared to measure variables. The variables measured were age, education, information, occupation, experience and environment. The research data analysis was univariate and bivariate analysis with chi square test. The results explained that there was a relationship between age (p=0.047), education (p=0.046), occupation (p=0.026), experience (p=0.016) with the mother's knowledge about baby massage. There was no relationship between information (p=0.110) and environment (p=0.801) with mothers' knowledge about infant massage. The conclusion of this study is that there is a relationship between age, education, occupation, and experience with mothers' knowledge about infant massage. Keywords: Age, Education, Occupation, Information, Experience, Environment, Knowledge, Massage, Infant ABSTRAK Pijat bayi memiliki banyak manfaat unutk kesehatan, salah satunya adalah kualitas tidur bayi. Pijat bayi tidak hanya dilakukan bila bayi sehat, tetapi juga pada bayi sakit atau rewel dan sudah menjadi rutinitas perawatan bayi setelah lahir Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan pengetahuan ibu tentang pijat bayi. Jenis penelitian yang digunakan adalah kuantitatif dengan menggunakan desain penelitian desain observasional analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah adalah semua ibu yang memiliki bayi 0-12 bulan yang berkunjung di RSUD Kota Sabang berjumlah 105 orang. Teknik pengambilan subjek menggunakan purposive sampling sebanyak 84 orang. Metode pengumpulan data yang digunakan adalah dengan menggunakan kuesioner yang disusun untuk mengukur variabel. Variabel yang diukur adalah usia, pendidikan, informasi, pekerjaan, pengalaman dan lingkungan. Analisa data penelitian adalah analisis univariat dan bivariat dengan uji chi square. Hasil penelitian menjelaskan bahwa terdapat hubungan usia (p=0,047), pendidikan (p= 0,046), pekerjaan (p=0,026), pengalaman (p=0,016) dengan pengetahuan ibu tentang pijat bayi. Tidak terdapat hubungan informasi (p=0,110) dan lingkungan (p=0,801) dengan pengetahuan ibu tentang pijat bayi. Kesimpulan penelitian ini adalah terdapat hubungan usia, pendidikan, pekerjaan, dan pengalaman dengan pengetahuan ibu tentang pijat bayi. Kata Kunci: Usia, Pendidikan, Pekerjaan, Informasi, Pengalaman, Lingkungan, Pengetahuan, Pijat, Bayi.